Studi Literatur: Analisis Kesulitan Belajar Siswa SMA pada Materi Matriks - M. Fauzan Zannurrain; Aulia Herdiyanti; Mega Utami Hasibuan (Department of Master Program on Mathematics Education Faculty of Teacher Training and Education State Islamic Institute of Lhokseumawe, Indonesia, 2023)
This research aims to conduct a literature study related to students' learning difficulties in the topic of matrices, and then describe the most dominant difficulties faced by students when learning the subject of matrices based on data summarized by researchers. The research utilizes the Systematic Literature Review (SLR) method to explain its findings. The data collection process begins with searching for relevant articles using Google Scholar and Repository. As a result, 23 articles relevant to this research were found. Next, out of these 23 articles, 18 articles were selected that met the criteria of suitability and relevance to this study. The selected articles cover a publication range from 2016 to 2023 to ensure that the data used are the most relevant and up-to-date since there were no articles matching this research before 2016. Based on the literature review conducted, the researchers can conclude several key points. The difficulties experienced by students include challenges in understanding concepts, difficulties in operations, difficulties in principles, and difficulties in knowledge or the application of facts. These key points were obtained from the conclusions of the 18 analyzed articles, where similar conclusions were identified and ranked based on the frequency of occurrence.